Dostęp do świadczeń opieki zdrowotnej na podstawie rozporządzenia w sprawie koordynacji systemów zabezpieczenia społecznego oraz dyrektywy transgranicznej. Próba porównania - Ilnicka-Jordan, Paulina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Access to healthcare services has guaranteed in the Constitution RP, domestic and international law. Public authority have to create principles of functioning and financing the health care system. The main law, which create principles of functioning and financing the health care system is the Act of 27 August 2004 on healthcare services financed from public funds. This Act establishes the waiting lists. These lists can be the reason of financing health care services abroad. The aim of this article is to show what kind of rights the patient has on the basic of the regulation on the coordination of social security systems and directive on the application of patient’s rights in cross-border healthcare
Keywords: patient; patient’s rights; cross-border healthcare